Analisis Metode Pembelajaran Guru PJOK Sebelum dan Sesudah Pandemi di SD Negeri 5 Besole, Besuki, Tulungagung - Restu Ajeng Selfina Maharani; Susi Susanti; Praticha Novianti Ramadhani; Rian Damariswara (LPPM Universitas PGRI Adi Buana Surabaya, 2022)
Due to the impact of the COVID-19 pandemic on the world of education, students study remotely or online. The purpose of this study was to determine the PJOK learning process before and after the covid-19 pandemic and the methods used in PJOK learning. This study uses a qualitative method with interview techniques that contain data or information from 1 teacher PJOK 5 Besole. From the results of the analysis of learning methods before the pandemic, 20% of lecture methods were used, 40% pratical methods, 10% question and answer method, 10% discussion methods, and 20% evaluation methods. Meanwhile, the learning method used after the pandemic is using the 50% lecture method, 20% question and answer method, and 30% evaluation method. And the most effective method used in the learning process before the pandemic is the practical method, because this method supports the corner learning process in skills assessment. While the most effective learning method used after the pandemic was the lecture method, because the practical method was temporarily removed due to the pandemic, learning was carried out online.